Isozyme variation in Passiflora subgenus Tacsonia : Geographic and interspecific differentiation among the three most common species - Segura, Sergio D.; Coppens d'Eeckenbrugge, Geo; Ocampo Nahar, César H.; Ollitrault, P (Springer, 2005)
In a general study of banana passion fruit genetic resources, diversity was analyzed in the two main cultigens, P. tripartita var. mollissima and P. tarminiana, and their closest wild relative, P. mixta, scoring isozyme bands (IDH,PGM,ACP,PGD,DIA,andPRX) on288 plants from 31 accessions. Polymorphismandallelic richness, Nei diversity indices, and neighbor joining clustering showed that variation was poor in the cultigens in northern and central Colombia, while P. mixta appeared much more polymorphic. The populations of P. tripartita var. mollissima and P. mixta from southern Colombia and Ecuador show higher diversity values and are clearly differentiated from those of central and northern Colombia. This geographic component of variation is even stronger than the interspecific one, which suggests a close relation and a regular gene flow between these two species. In contrast, all the accessions of P. tarminiana constitute a clearly differentiated group, even if some introgression with P. tripartita var. mollissima is also suspected. The high variation observed in the southern region indicates the proximity of a center of diversity for banana passion fruit and collecting in Ecuador, Peru and Bolivia is recommended. The high diversity of P. mixta and the evidence of gene flow with P. tripartita var. mollissima constitute a favorable context for the implementation of in situ conservation strategies.